Puerperae bonding with their children and labor experiences - Helk Souza, Lara; Sperli Geraldes Soler, Zaida Aurora; Sperli Geraldes Santos, Maria de Lourdes; Sperli Geraldes Marin dos Santos, Natália (Investigación y Educación en Enfermería, 2017)
Objective. To analyze the degree of bonding of puerperae with their babies, both in isolation and associated with experiences during and after labor. Methods. A crosssectional study carried out among 200 puerperae in São José do Rio Preto, Brazil. To evaluate the motherchild bond, we used the Mother-to-Infant Bonding Scale (MIBS). Results. The mean age of puerperae was 26.4 years; most women were white (60.0%), were married (87.5%), and had an elementary education (51.5%). Most deliveries were cesarean (80.0% of cases); 68.0% of women had no pain during labor, and only 54% had skin-to-skin contact immediately after delivery. Type of labor and pain did not significantly change the maternal bond, and the lack of skin-to-skin contact negatively influenced the bond. Conclusion. Pueperae participants had a high degree of bonding with their babies that is mainly related to history of skin-to-skin contact. Nurses must promote strategies that encourage skin-to-skin contact between mother and newborn in the delivery room. How to cite this article: Souza LH, ZASG Soler, Santos MLSG, Sasaki NSGMS. Puerperae bonding with their children and labor experiences. Invest. Educ. Enferm. 2017; 35(3):364-371.